132 Describing deprescribing – when are we stopping medications in palliative care?. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Doré, Matthew; Fox, Hannah; Campbell, Trish; Willis, Derek
Abstract : Introduction: Deprescribing is the process of withdrawal of medication with the goal of improving patient care. Research currently is in the context of polypharmacy and geriatrics, however despite its ubiquity within palliative care there is a paucity of research in this context. Anecdotally, deprescribing is performed adhoc and using 'common sense' but there appears no clear data on rational, benefit and whole numbers involved. Aim: To gather data on current deprescribing practice within palliative care, with the aim to inform our own specialty and others. Methodology: Prospectively palliative in-patient hospice and community patients had medications deprescribed recorded and the rational. This was prospectively gaining a timeline of medication stops respective to date of death. Results: Data collected from 13/3/18 to 30/06/18 with 647 medication stops of 197 differing medications. 56% (361) medication stops were due to approaching end-of-life. 15% (93) due to swallowing difficulties, 17% (109) due to rationalising medications. The median number of days of palliative care deprescribing any medication before death is 4, with 25% being 1 day and 75% being 9 days before death. Groups were identified and individually measured, including statins (median 5 days), Beta-blockers (median 2), ACEi (median 5), anti-platelets (median 9), Warfarin/NOACS (median 5). Conclusion/discussion: By describing deprescribing current practice we outline the short timespan between deprescribing and death for medications arguably of minimal patient benefit at this point in life. The rational for stopping correlates with this postulation, outlining we are stopping the vast majority of medications due to the dying phase rather than preemptively.